IbM Rice Farmers Empowerment Using SRI (System of Rice Intensification) in District Namorambe - Simanungkalit, Ferlando Jubelito (Journal of Saintech Transfer, 2019)
IbM Rice Farmers Empowerment Using SRI (System of Rice Intensification) in District Namorambe was held in Namorambe and Cinta Rakyat Village involving two partners who work as rice farmers. The problems of Mitra 1 in Namorambe Village are (a) number of seeds used 40-50 kg / ha, (b) seed age 20-25 days, (c) planting range 15x15 cm, (e) number of planting plants 4-5 seedlings (f) artificial fertilizer 400kg urea / ha + 150kg SP-36 / ha + 150kg KCl / ha, (g) watering elevation 20-25 cm. The problems of Mitra 2 in Cinta Rakyat Village are (a) the remaining rice straw is not processed, (b) the haystack becomes the pest of rats and fungi, (c) the soil hardens and quickly dries, (d) the straw is burned. IbM program is implemented using participatory approach, training, extension method and descriptive approach method. Impact of empowerment at Mitra 1 has been able to carry out the manufacture of paddy field plot of SRI method with production of 875 kg / 1000 mÂ² (8.75 tons / ha); an increase in production of about 3.45 tons / ha or equivalent to 65.09%. Impact of empowerment at Mitra 2 that has been able to produce organic fertilizer from the remaining straw; has been able to manage the remaining rice straw to prevent pests and diseases; not burn the rest of the straw; and able to utilize organic fertilizer to enrich the soil.